Silicon-carbon composite material, negative pole piece, battery monomer and electric device

Through electrostatic action, the carbon-containing material and the silicon-containing material are combined to form a silicon-carbon composite material and used for the negative electrode film layer, which solves the problem of poor cycle life and use reliability of the negative electrode active material in the prior art, and achieves a higher Structural stability and conductivity.

CN119480941AActive Publication Date: 2025-02-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311017409.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-11
Publication Date
2025-02-18
Estimated Expiration
2043-08-11

AI Technical Summary

Technical Problem

The existing negative electrode active materials have poor cycle life and reliability in battery cells.

Method used

Electrostatic action is used to combine carbon-containing materials with silicon-containing materials to form silicon-carbon composite materials, which are used in the negative electrode film layer, and the structural strength and conductivity of the material are improved through electrostatic action.

Benefits of technology

It improves the cycle life and reliability of battery cells, and enhances the structural stability and conductivity of silicon-carbon composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480941A_ABST
    Figure CN119480941A_ABST
Patent Text Reader

Abstract

The invention relates to a silicon-carbon composite material, a negative pole piece, a battery monomer and an electric device, the silicon-carbon composite material comprises a carbon-containing material and a silicon-containing material, and the carbon-containing material comprises a carbon-based substance and a first group arranged on the surface of the carbon-based substance; the silicon-containing material comprises a silicon-based substance and an organic compound coating at least part of the surface of the silicon-based substance, the electrical properties of the organic compound and the first group are opposite, and the organic compound and the first group are combined through electrostatic interaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a silicon-carbon composite material, a negative electrode sheet, a battery cell and an electrical device. Background Art

[0002] Battery cells have the characteristics of high capacity and long life, so they are widely used in electronic devices such as mobile phones, laptops, electric vehicles, electric cars, electric ships, electric toy cars, electric toy ships, electric toy planes and electric tools, etc. Due to the great progress made in battery cells, higher requirements are placed on the performance of battery cells. In order to improve the performance of battery cells, the materials in the battery cells, such as negative electrode active materials, are usually optimized and improved. As the carrier of metal ions and electrons in the battery cells, the negative electrode active materials play the role of energy storage and release, and have a non-negligible impact on the performance of the battery cells.

[0003] However, when the improved negative electrode active materials are applied to battery cells, the cycle life and reliability of the battery cells are still poor. Summary of the invention

[0004] The present application provides a silicon-carbon composite material, a negative electrode plate, a battery cell and an electrical device. The cycle performance and storage performance of the battery cell described in the present application can be improved.

[0005] In a first aspect, an embodiment of the present application proposes a silicon-carbon composite material, wherein the silicon-carbon composite material includes a carbon-containing material and a silicon-containing material, wherein the carbon-containing material includes a carbon-based substance and a first group disposed on the surface of the carbon-based substance; the silicon-containing material includes a silicon-based substance and an organic compound coated on at least a portion of the surface of the silicon-based substance, wherein the organic compound and the first group have opposite electrical properties, and the organic compound and the first group are bonded by electrostatic action.

[0006] Therefore, in the embodiment of the present application, the silicon-containing material can increase the active ion storage capacity, the organic compound on the surface of the silicon-containing material can enhance the physical crosslinking with the carbon-containing material, and the structural strength of the silicon-carbon composite material formed by the composite of the two is improved; the carbon-containing material can buffer the volume change of the silicon-containing material, improve the electronic conductivity of the silicon-carbon composite material, and can reduce the volume change of the silicon-containing material, and reduce the risk of breakage and reformation of the SEI film, thereby taking into account both improving the cycle life and reliability of the battery cell.

[0007] In some embodiments, the first group is at least one of a hydroxyl group (-OH), an amino group (-NH2), an alkyl group (-R1), an acyloxy group (-OCOR2) and an alkoxy group (-OR3). This configuration enables the carbon-containing material and the silicon-containing material to be combined by electrostatic interaction.

[0008] In some embodiments, the organic compound includes a positively charged group; optionally, the organic compound includes at least one of polydiallyldimethylammonium chloride (PDDA), polyacrylamide (PAM), and polydimethyldiallylammonium chloride (PDMDAAC). This configuration enables the carbon-containing material and the silicon-containing material to be combined through electrostatic interaction.

[0009] In some embodiments, the carbon-based material includes at least one of natural graphite, artificial graphite, graphene, carbon nanotubes and carbon fibers; and / or the silicon-based material includes at least one of silicon and silicon oxide; optionally, the silicon includes at least one of silicon nanoparticles and silicon micron-particles; further optionally, the silicon nanoparticle includes at least one of silicon nanoparticles, silicon nanowires and silicon nanosheets. The above silicon-based materials can be combined with carbon-based materials in an electrostatic manner, which is beneficial to improve the potential of embedded active ions in silicon-carbon composite materials and improve the reliability of battery cells.

[0010] In some embodiments, the carbon-based substance includes at least one of carbon nanotubes and carbon fibers; optionally, the carbon nanotubes include at least one of single-walled carbon nanotubes and multi-walled nanotubes; the silicon-based substance includes silicon nanoelement; optionally, the silicon-based substance includes silicon nanowires.

[0011] Therefore, in the embodiment of the present application, the carbon-based substance and the silicon-based substance are both low-dimensional materials, the carbon-containing material formed by the combination of the carbon-based substance and the first group is also a low-dimensional material, and the silicon-containing material formed by the combination of the silicon-based substance and the organic compound is also a low-dimensional material. When the carbon-containing material and the silicon-containing material are compounded, the two can cross-link to form a two-dimensional material. Since the silicon-carbon composite material has a stable cross-linked structure, the carbon-containing material and the silicon-containing material can be understood as mutually entangled structural forms, which is conducive to the winding of the carbon-containing material to reversely reduce the stress generated by the silicon-containing material, reduce the degree of volume expansion of the silicon-containing material, and improve the stability of the overall structure of the silicon-carbon composite material.

[0012] In some embodiments, based on the total mass of the silicon-carbon composite material, the ratio of the mass content of the carbon-containing material to the mass content of the silicon-containing material is (3 to 5): 1; optionally, the mass content of the carbon-containing material is 75% to 85%; and / or the mass content of the silicon-containing material is 15% to 25%.

[0013] Therefore, when the ratio of the mass content of the carbon-containing material to the mass content of the silicon-containing material in the embodiment of the present application is within the above range, the carbon-containing material can significantly improve the volume expansion effect of the silicon-containing material and improve the structural stability of the silicon-carbon composite material; and the electrical conductivity of the silicon-carbon composite material can be improved.

[0014] In some embodiments, based on the total mass of the silicon-carbon composite material, the ratio of the mass content of the organic compound to the mass content of the silicon-based substance is (1 to 5): 20; optionally, the mass content of the organic compound is 1% to 5%; and / or the mass content of the silicon-based substance is 15% to 20%.

[0015] Therefore, when the ratio of the mass content of the organic compound to the mass content of the silicon-based substance in the embodiment of the present application is within the above range, the organic compound can provide relatively more second groups for the silicon-based substance, which helps to evenly distribute the silicon-containing material and the carbon-containing material, and is beneficial to the cross-linking of the silicon-containing material and the carbon-containing material to form a structurally stable silicon-carbon composite material.

[0016] In some embodiments, the silicon-carbon composite material satisfies at least one of conditions (1) to (3):

[0017] (1) The volume average particle size Dv50 of the silicon-carbon composite material is 1 μm to 5 μm;

[0018] (2) The BET specific surface area of ​​the silicon-carbon composite material is 200 m 2 / g to 400m 2 / g;

[0019] (3) The electrical conductivity of the silicon-carbon composite material is 120 S / cm to 3000 S / cm; optionally, 300 S / cm to 3000 S / cm.

[0020] Therefore, when the silicon-carbon composite material according to the embodiment of the present application meets the above conditions, the cycle life and the reliability of use of the battery cell can be further improved.

[0021] In the second aspect, the present application proposes a method for preparing a silicon-carbon composite material, comprising providing a carbon-based substance; subjecting the carbon-based substance to a grouping treatment so that the surface of the carbon-based substance has a first group and a carbon-containing material is formed; providing a silicon-based substance; providing an organic compound to the silicon-based substance for a grouping treatment so that at least a portion of the surface of the silicon-based substance is coated with the organic compound and a silicon-containing material is formed, wherein the electrical properties of the organic compound and the first group are opposite; mixing the carbon-containing material and the silicon-containing material to obtain a silicon-carbon composite material, wherein the first group and the organic compound are combined by electrostatic action.

[0022] In a third aspect, the present application proposes a negative electrode plate, comprising a negative electrode current collector and a negative electrode film layer arranged on at least one side of the negative electrode current collector, the negative electrode film layer comprising the silicon-carbon composite material as described in any embodiment of the first aspect of the present application, or the silicon-carbon composite material as described in any embodiment of the second aspect of the present application.

[0023] In some embodiments, the bonding force of the negative electrode plate is 15 N / m to 20 N / m; optionally 17 N / m to 20 N / m; and / or the negative electrode plate is 1×10 4 Under a force of Kg (10T), the elongation is 1.5% to 2.5%; optionally, 1.8% to 2.5%.

[0024] In a fourth aspect, the present application proposes a battery cell, comprising a negative electrode plate as described in any embodiment of the third aspect of the present application.

[0025] In a fifth aspect, the present application further proposes an electrical device, comprising a battery cell as described in any embodiment of the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.

[0027] Figure 1 It is a schematic diagram of an embodiment of a battery cell of the present application.

[0028] Figure 2 yes Figure 1 An exploded schematic diagram of an embodiment of a battery cell.

[0029] Figure 3 It is a schematic diagram of an embodiment of a battery module of the present application.

[0030] Figure 4 It is a schematic diagram of an embodiment of the battery pack of the present application.

[0031] Figure 5 yes Figure 4 An exploded schematic diagram of an embodiment of a battery pack is shown.

[0032] Figure 6 It is a schematic diagram of an embodiment of an electric device including the battery cell of the present application as a power source.

[0033] Figure 7 It is a schematic diagram of the preparation of the silicon-carbon composite material in Example 1 of the present application.

[0034] Figure 8 This is the infrared spectrum of the single-walled carbon nanotube MWCTN after acid treatment in Example 1 of the present application.

[0035] Fig. 9This is a zeta potential test graph of the acid-treated MWCNT and the PDDA-treated silicon nanowire PDDA-Si in Example 1 of the present application.

[0036] The drawings are not necessarily drawn to scale.

[0037] The following are the descriptions of the reference numerals:

[0038] 1. Battery pack; 2. Upper box; 3. Lower box; 4. Battery module;

[0039] 5. Battery cell; 51. Housing; 52. Electrode assembly;

[0040] 53. Cover plate;

[0041] 6. Electrical equipment. DETAILED DESCRIPTION

[0042] Hereinafter, the embodiments of the silicon-carbon composite material, negative electrode sheet, battery cell, battery and electrical device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0043] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0044] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0045] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0046] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0047] As the application scope of battery cells expands, the requirements for battery cell performance, such as energy density, are gradually increasing. The negative electrode film layer has a significant impact on the performance of battery cells. Carbon and silicon, as common materials for negative electrode films, have been widely studied.

[0048] The theoretical specific capacity of carbon is low, and its lithium insertion potential is low, which can easily cause lithium precipitation and lead to reliability problems. The theoretical specific capacity of silicon is high, up to 4200mAh / g, and its lithium insertion potential is slightly higher than that of graphite, which can reduce the risk of lithium precipitation. However, many disadvantages of silicon have hindered its application. First, in terms of electron transport, the conductivity of silicon is only 10 -3 S / cm, the lithium ion diffusion coefficient is 10 -12 cm -2 / s, the charge transfer dynamics are poor during the charge and discharge process, thus limiting the rate performance of silicon. The volume change of silicon during the lithium insertion and extraction reaction may be greater than 300%. The large volume change and the silicon particles with constantly changing volumes are likely to cause the solid electrolyte interface film (Solid-Electrolyte Interphase, SEI film) on the surface of the active material to rupture and regenerate. The repeated growth of the SEI film will not only continuously consume lithium and electrolyte, but also limit the transmission of lithium ions, reduce the electrical contact of the active material, and increase the impedance; and the micron-scale silicon material will also have the phenomenon of rupture and pulverization. After rupture and pulverization, the fresh silicon surface is continuously exposed, forming a new SEI film, increasing the thickness of the SEI film, resulting in an extension of the lithium ion transmission path, making the cycle life of the battery cell shorter.

[0049] In view of the advantages and disadvantages of carbon and silicon, the relevant technology considers compounding carbon-containing materials and silicon-containing materials. However, the simple compound operation cannot effectively improve the structural stability of the negative electrode film layer, and cannot take into account the improvement of the cycle life and reliability of the battery cell.

[0050] The embodiment of the present application uses electrostatic action to compound the carbon-containing material and the silicon-containing material. The introduction of the carbon-containing material can improve the conductivity of the silicon-carbon composite material and improve the electronic conductivity; the introduction of the silicon-containing material can improve the specific capacity of the silicon-carbon composite material, and can reduce the risk of precipitation of active metals during the cycle, and improve the reliability of the battery cell; and because the carbon-containing material and the silicon-containing material are combined through electrostatic action, the distribution uniformity of the carbon-containing material and the silicon-containing material is improved, the silicon-containing material is surrounded by the carbon-containing material, and the carbon-containing material acts as a buffer layer for silicon expansion, which can reduce the risk of silicon expansion, thereby reducing the risk of silicon-containing material being pulverized, and improving the overall structural stability of the silicon-carbon composite material. The organic compound on the surface of the silicon-containing material can enhance the physical crosslinking with the carbon-containing material, and the structural strength of the silicon-carbon composite material formed by the two is further improved, so that the cycle life of the battery cell can be improved. Next, the technical solution of the present application is described in detail.

[0051] Silicon Carbon Composite Materials

[0052] In the first aspect, the present application proposes a silicon-carbon composite material. The silicon-carbon composite material is used in the negative electrode film layer as a negative electrode active material. The silicon-carbon composite material includes a carbon-containing material and a silicon-containing material, the carbon-containing material includes a carbon-based substance and a first group disposed on the surface of the carbon-based substance, and the silicon-containing material includes a silicon-based substance and an organic compound coated on at least part of the surface of the silicon-based substance, the organic compound and the first group have opposite electrical properties, and the organic compound and the first group are combined by electrostatic action.

[0053] The carbon-containing material includes a first group, and the silicon-containing material includes an organic compound. The first group and the organic compound have opposite electrical properties, which can be equivalent to the organic compound including a second group with opposite electrical properties to the first group. It can be understood that the first group is negatively charged relative to the second group, and correspondingly, the second group is positively charged relative to the first group; or, the first group is positively charged relative to the second group, and correspondingly, the second group is negatively charged relative to the first group. Since the first group and the second group have opposite electrical properties, the two can be combined by electrostatic action, so that the carbon-based material and the silicon-based material are combined by Coulomb interaction, that is, they are combined in an electrostatic way, so that the distribution of the carbon-containing material and the silicon-containing material is more uniform, that is, the distribution uniformity is improved. Since the potential of the active ions embedded in the silicon-containing material is relatively high, the risk of active metal precipitation can be reduced, and the reliability of the battery cell can be improved.

[0054] Since there are organic compounds on the surface of the silicon-containing material, the organic compounds can be combined with the silicon-based material in the form of covalent bonds, and the organic compounds can attract the first group. It can be understood that the carbon-containing material is distributed on the periphery of the silicon-containing material. The introduction of the carbon-containing material can increase the rate of electron conduction to the silicon-containing material, thereby improving the overall conductivity of the carbon-silicon composite material; in addition, the carbon-containing material can serve as a buffer layer for silicon expansion, which can buffer the expansion degree of the silicon-containing material, thereby reducing the risk of pulverization of the silicon-containing material and improving the overall structural stability of the silicon-carbon composite material, thereby taking into account the improvement of the cycle life of the battery cell.

[0055] In addition, since the silicon-based surface is coated with organic compounds, the organic compounds provide charged groups for the silicon-containing material on the one hand, which is conducive to the combination of the silicon-containing material and the carbon-containing material through electrostatic action; on the other hand, the setting of the organic compounds can provide more active sites on the surface of the silicon-containing material to load more charged groups, so that the combination of the silicon-containing material and the carbon-containing material is tighter, and the organic compounds on the surface of the silicon-based material are equivalent to the effect of grafting branches on the surface of the silicon-based material, which can enhance the physical cross-linking between the silicon-containing material and the carbon-containing material and improve the structural strength of the silicon-carbon composite material; on the other hand, the organic compounds are coated on the outside of the silicon-based material, which can play a certain volume buffering role on the silicon-based material, reduce the risk of excessive volume expansion of the silicon-containing material, and further improve the overall structural stability of the silicon-carbon composite material, so as to improve the cycle life of the battery cell. Due to the cross-linked structure of the silicon-carbon composite material, it has good flexibility and structural stability. When it is added to the negative electrode plate as a negative active material, it can improve the toughness of the negative electrode film layer, and the negative electrode film layer is not easy to crack, etc., and the structural stability of the negative electrode plate is relatively high.

[0056] Therefore, in the embodiment of the present application, the silicon-containing material can increase the active ion storage capacity, the organic compound on the surface of the silicon-containing material can enhance the physical crosslinking with the carbon-containing material, and the structural strength of the silicon-carbon composite material formed by the composite of the two is improved; the carbon-containing material can buffer the volume change of the silicon-containing material, improve the electronic conductivity of the silicon-carbon composite material, and can reduce the volume change of the silicon-containing material, and reduce the risk of breakage and reformation of the SEI film, thereby taking into account both improving the cycle life and reliability of the battery cell.

[0057] In some embodiments, the first group may be a negatively charged group; accordingly, the second group in the organic compound may be a positively charged group. This arrangement enables the carbon-containing material and the silicon-containing material to be combined through electrostatic interaction.

[0058] Exemplarily, the first group includes at least one of a hydroxyl group (-OH), an amino group (-NH2), an alkyl group (-R1), an acyloxy group (-OCOR2) and an alkoxy group (-OR3). Optionally, the first group may include a hydroxyl group. Among them, the alkyl-R1 may be a substituted or unsubstituted C1 to C10 alkyl group, such as a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, etc.; the acyloxy group may be a formyloxy group, an acetoxy group, a propionyloxy group, a butyryloxy group, a pentyloxy group, a hexyloxy group, etc.; the alkoxy group may be a substituted or unsubstituted C1 to C10 alkoxy group, such as a methoxy group, an ethoxy group, a propoxy group, a butoxy group, a pentyloxy group, a hexyloxy group, etc.; the carbon chain of the above groups is relatively short, and the steric hindrance is relatively small, which is conducive to the combination of carbon-containing materials and silicon-containing materials. When the above groups are substituted, the substituent groups may include halogen atoms, such as fluorine atoms, chlorine atoms, etc.

[0059] Specifically, the positively charged organic compound may include at least one of polydiallyldimethylammonium chloride (PDDA), polyacrylamide (PAM), and polydimethyldiallylammonium chloride (PDMDAAC).

[0060] The above-mentioned organic compounds have good chemical stability and excellent deformation ability. During the process of active ion extraction and / or embedding into silicon-based substances, the organic compounds can shrink or stretch synchronously with the silicon-based substances, so that the silicon-based substances can adapt to larger volume changes and improve the overall structural stability of the silicon-carbon composite material.

[0061] In some embodiments, the carbon-based material includes at least one of natural graphite, artificial graphite, graphene, carbon nanotubes CNTs and carbon fibers CNFs. The above carbon-based materials can be combined with silicon-based materials in an electrostatic manner, which is beneficial to improve the conductivity of silicon-carbon composite materials and improve the rate performance. In addition, the carbon-based material can also relieve the internal stress generated during the charge and discharge process and buffer the volume change of the silicon-containing material.

[0062] Optionally, the carbon-based material includes at least one of carbon nanotubes CNTs and carbon fibers CNFs; further optionally, the carbon-based material includes at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes. The above-mentioned carbon-based material is a low-dimensional carbon material (such as one-dimensional), which can effectively construct a conductive network, promote the effective transmission of electrons and the rapid transfer of electrons, and can relieve the stress caused by the expansion of silicon-containing materials, reduce the risk of pulverization of silicon-containing materials, and improve the stability of the overall structure of silicon-carbon composite materials.

[0063] In some embodiments, the silicon-based material includes at least one of silicon and silicon oxide. The above silicon-based materials can be electrostatically combined with the carbon-based material, which is beneficial to improve the potential of embedded active ions in the silicon-carbon composite material and improve the reliability of the battery cell.

[0064] Optionally, the silicon-based material may be a nano material, for example, silicon oxide may be nano silicon oxide, and silicon element may be silicon nano element. Nano-scale silicon-based materials can significantly reduce their own volume expansion effect. Of course, the silicon-based material may be a micron material, for example, silicon oxide may be micron silicon oxide, and silicon element may be silicon micron element.

[0065] Optionally, the silicon nano-substance may include at least one of silicon nanoparticles, silicon nanowires and silicon nanosheets. Nano-scale silicon-based materials can significantly reduce their own volume expansion effect, help improve their own structural stability; and can reduce the repeated formation of SEI film on the surface of silicon-containing materials during the cycle process, thereby improving the cycle performance and reliability of battery cells.

[0066] For example, silicon nanoparticles may include silicon quantum dots, etc. Silicon quantum dots may be understood as silicon nanoparticles with three dimensions less than 100 nm, similar to dot-shaped objects. Of course, silicon nanoparticles may also include silicon nanoparticles with at least one dimension greater than or equal to 100 nm.

[0067] For example, the silicon-based material may include silicon nanowires. The dimensions of silicon nanowires are relatively low, which is conducive to the composite of silicon nanowires and carbon-containing materials.

[0068] In some embodiments, the carbon-based material may include at least one of carbon nanotubes and carbon fiber tubes; the carbon nanotubes may include at least one of single-walled carbon nanotubes and multi-walled nanotubes; and the silicon-based material may include silicon nanowires. Both the carbon-based material and the silicon-based material are low-dimensional materials, for example, both are one-dimensional materials. The carbon-containing material formed by the combination of the carbon-based material and the first group is also a low-dimensional material. The silicon-containing material formed by the combination of the silicon-based material and the organic compound is also a low-dimensional material. When the carbon-containing material and the silicon-containing material are composited, the two can be cross-linked to form a two-dimensional material. Since the silicon-carbon composite material has a stable cross-linked structure, the carbon-containing material and the silicon-containing material can be understood as a mutually entangled structural form, which is conducive to the winding of the carbon-containing material to reduce the stress generated by the silicon-containing material, reduce the degree of volume expansion of the silicon-containing material, and improve the stability of the overall structure of the silicon-carbon composite material. And since the silicon-carbon composite material has a stable cross-linked structure, it can increase the viscosity of the negative electrode slurry, reduce the amount of binder, and increase the amount of the negative electrode film layer to improve the energy density of the battery cell; and it can also improve the stability of the negative electrode film layer formed by the negative electrode slurry.

[0069] Exemplarily, the silicon-based substance includes carbon nanotubes; the silicon-based substance includes silicon nanowires.

[0070] Optionally, the diameter of the carbon nanotube is 5 nm to 20 nm, and / or the length of the carbon nanotube is 1 μm to 5 μm. When the size of the carbon nanotube is within the above range, it is beneficial to crosslink with the low-dimensional silicon-containing material.

[0071] For example, the diameter of the carbon nanotubes can be 5nm, 5.5nm, 6nm, 6.5nm, 7nm, 7.5nm, 8nm, 8.5nm, 9nm, 9.5nm, 10nm, 10.5nm, 11nm, 11.5nm, 12nm, 12.5nm, 13nm, 13.5nm, 14nm, 14.5nm, 15nm, 15.5nm, 16nm, 16.5nm, 17nm, 17.5nm, 18nm, 18.5nm, 19nm, 19.5nm, 20nm, or a range consisting of any two of the above values.

[0072] For example, the length of the carbon nanotubes may be 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, or a range consisting of any two of the above values.

[0073] Optionally, the diameter of the silicon nanowire is 50 nm to 100 nm, and / or the length of the silicon nanowire is 1 μm to 10 μm. When the size of the carbon nanotube is within the above range, it is beneficial to crosslink with low-dimensional carbonaceous materials.

[0074] For example, the diameter of the silicon nanowire may be 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, or a range consisting of any two of the above values.

[0075] For example, the length of the silicon nanowire can be 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, or a range consisting of any two of the above values.

[0076] In the embodiments of the present application, the diameters of carbon nanotubes and silicon nanowires have well-known meanings in the art and can be detected using equipment and methods commonly used in the art. For example, characterization tests can be performed using a scanning electron microscope SEM (eg, ZEISS Sigma 300).

[0077] In some embodiments, based on the total mass of the silicon-carbon composite material, the ratio of the mass content of the carbon-containing material to the mass content of the silicon-containing material is (3 to 5): 1. When the ratio of the mass content of the carbon-containing material to the mass content of the silicon-containing material is within the above range, the carbon-containing material can significantly improve the volume expansion effect of the silicon-containing material and improve the structural stability of the silicon-carbon composite material; and the electrical conductivity of the silicon-carbon composite material can be improved.

[0078] Exemplarily, the mass content of the carbon-containing material is 75% to 85%. When the mass content of the carbon-containing material is within the above range, the structural stability of the silicon-carbon composite material can be significantly improved.

[0079] For example, the mass content of the carbonaceous material can be 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85% or a range consisting of any two of the above values.

[0080] Exemplarily, the mass content of the silicon-containing material is 15% to 25%. When the mass content of the silicon-containing material is within the above range, the structural stability of the silicon-carbon composite material can be significantly improved.

[0081] For example, the mass content of the silicon-containing material may be 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25% or a range consisting of any two of the above values.

[0082] In some embodiments, based on the total mass of the silicon-carbon composite material, the ratio of the mass content of the organic compound to the mass content of the silicon-based substance is (1 to 5): 20. When the ratio of the mass content of the organic compound to the mass content of the silicon-based substance is within the above range, the organic compound can provide relatively more second groups for the silicon-based substance, which helps to evenly distribute the silicon-containing material and the carbon-containing material, and is conducive to the cross-linking of the silicon-containing material and the carbon-containing material to form a structurally stable silicon-carbon composite material, and will not form an excessively thick coating layer on the silicon-based substance, which affects the transmission of active ions such as lithium ions.

[0083] Exemplarily, the mass content of the organic compound is 1% to 5%.

[0084] For example, the mass content of the organic compound may be 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or a range consisting of any two of the above values.

[0085] Exemplarily, the mass content of the silicon-based substance is 15% to 20%.

[0086] For example, the mass content of the silicon-based substance may be 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20% or a range consisting of any two of the above values.

[0087] In order to further improve the cycle life and reliability of battery cells, the embodiments of the present application may further select the physical and chemical parameters of the silicon-carbon composite material.

[0088] In some embodiments, the volume average particle size Dv50 of the silicon-carbon composite material is 1 μm to 5 μm.

[0089] For example, the volume average particle size Dv50 of the silicon-carbon composite material may be 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, or a range consisting of any two of the above values.

[0090] In the embodiment of the present application, the volume average particle size Dv50 of the material has a well-known meaning in the art. For example, the volume average particle size Dv50 of the material refers to the particle size corresponding to 50% in the volume distribution. It can be detected by using equipment and methods commonly used in the art. For example, a silicon-carbon composite material is taken as a sample, and the volume average particle size Dv50 is tested by a Mastersizer 2000E laser particle size analyzer according to the test standard GB / T 19077-2016.

[0091] In some embodiments, the BET specific surface area of ​​the silicon-carbon composite material is 200 m 2 / g to 400m 2 / g.

[0092] For example, the BET specific surface area of ​​the silicon-carbon composite material can be 200 m 2 / g, 210m 2 / g, 220m 2 / g, 230m 2 / g, 240m 2 / g, 250m 2 / g, 260m 2 / g, 270m 2 / g, 280m 2 / g, 290m 2 / g、300m 2 / g, 310m 2 / g, 320m 2 / g, 330m 2 / g, 340m 2 / g, 350m 2 / g, 360m 2 / g, 370m 2 / g, 380m 2 / g, 390m 2 / g, 400m 2 / g or a range consisting of any two of the above values.

[0093] In the embodiments of the present application, the BET specific surface area of ​​the silicon-carbon composite material has a well-known meaning in the art and can be detected by using equipment and methods commonly used in the art. For example, the silicon-carbon composite material is taken as a sample and calculated according to the BET (Brunauer Emmett Teller) method in accordance with the test standard GB / T19587-2017. Specifically, the specific surface area can be tested by a Tri-Star 3020 specific surface area pore size analysis tester produced by Micromeritics, USA.

[0094] In some embodiments, the electrical conductivity of the silicon-carbon composite material is 120 S / cm to 3000 S / cm; optionally 300 S / cm to 3000 S / cm. Exemplarily, the electrical conductivity of the silicon-carbon composite material can be 120 S / cm, 150 S / cm, 200 S / cm, 300 S / cm, 400 S / cm, 500 S / cm, 600 S / cm, 700 S / cm, 800 S / cm, 900 S / cm, 1000 S / cm, 1200 S / cm, 1300 S / cm, 1500 S / cm, 1600 S / cm, 1700 S / cm, 1800 S / cm, 1900 S / cm, 2000 S / cm, 2100 S / cm, 2200 S / cm, 2300 S / cm, 2400 S / cm, 2500 S / cm, 2600 S / cm, 2700 S / cm, 2800 S / cm, 2900 S / cm, or a range consisting of any two of the above values.

[0095] Since carbon-containing materials are added to silicon-carbon composite materials, the conductivity of silicon-carbon composite materials can be significantly improved, for example, by adding single-walled carbon nanotubes, multi-walled carbon nanotubes, etc. to improve the conductivity of the material as a whole. When the silicon-carbon composite material forms a cross-linked structure, the cross-linked network helps to form a conductive network, thereby improving the conductivity.

[0096] In the embodiment of the present application, the electrical conductivity of the silicon-carbon composite material is well known in the art and can be tested using equipment and methods commonly used in the art, such as taking the silicon-carbon composite material as a sample and testing it using a powder resistance instrument.

[0097] Method for preparing silicon-carbon composite material

[0098] In a second aspect, the present application also proposes a method for preparing a silicon-carbon composite material.

[0099] The method comprises:

[0100] Step S100, providing a carbon-based substance;

[0101] Step S200, performing grouping treatment on the carbon-based substance so that the surface of the carbon-based substance has a first group and forms a carbon-containing material;

[0102] Step S300, providing a silicon-based material;

[0103] Step S400, providing an organic compound to the silicon-based material for grouping treatment, so that at least a portion of the surface of the silicon-based material is coated with the organic compound, and a silicon-containing material is formed, wherein the electrical properties of the organic compound and the first group are opposite;

[0104] Step S500, mixing the carbon-containing material and the silicon-containing material to obtain a silicon-carbon composite material, wherein the first group and the organic compound are combined by electrostatic interaction.

[0105] The silicon-carbon composite material prepared by the method proposed in the embodiment of the present application has excellent cycle life and reliability when applied to battery cells.

[0106] In some embodiments, the carbon-based substance may include at least one of natural graphite, artificial graphite, graphene, carbon nanotubes CNTs, and carbon fibers CNFs.

[0107] In some embodiments, the silicon-based material includes at least one of silicon element and silicon oxide.

[0108] In some embodiments, in step S200, the carbon-based material may be treated with a compound containing a first group, for example,

[0109] The hydroxyl-containing compound includes at least one of methanol, ethanol, ethylene glycol, sulfuric acid, and nitric acid;

[0110] The amino group-containing compound includes at least one of an amine, an amide or an amino acid;

[0111] The alkyl-containing compound includes at least one of methane, dimethyl sulfate or methyl iodide;

[0112] The alkoxy-containing compound includes at least one of ether, acetaldehyde or methylamine;

[0113] The acyloxy group-containing compound includes at least one of acryloxypropionic acid or 4-acetoxystyrene.

[0114] In some embodiments, step S200 may include: subjecting the carbon-based substance to an acid treatment so that the surface of the carbon-based substance has a first group and forms a carbon-containing material, wherein the first group is a negatively charged group. The acid treatment can reduce the dangling bonds and carbon-oxygen bonds on the surface of the carbon-based substance to obtain a carbon-based substance modified with a surface carrying a negatively charged group. The acid treatment can cause the surface of the carbon-based substance to carry a negatively charged group, which is conducive to combining with the carbon-containing material through electrostatic action.

[0115] Specifically, the carbon-based substance and the mixed acid can be mixed and ultrasonically treated for 2.5 to 3 hours, filtered using a polytetrafluoroethylene filter membrane, and rinsed with deionized water 3-5 times until the pH of the filtrate is 6±0.5. After filtration, it can be dried in a freeze drying oven at -50°C for 12 hours and then used.

[0116] Optionally, the mixed acid includes at least two of concentrated sulfuric acid, concentrated nitric acid and concentrated phosphoric acid. Optionally, the mass ratio of the acids in the mixed acid may be 1:1.

[0117] Optionally, based on the total mass of the carbon-based substance and the mixed acid, the ratio of the mass content of the carbon-based substance to the mass content of the mixed acid is (1 to 2):200.

[0118] In some implementations, step S400 may include:

[0119] The mixed ammonia water, hydrogen peroxide and silicon-based substance are ultrasonically treated for 35 to 45 minutes to obtain a mixed intermediate; the silicon-based substance is treated with ammonia water and hydrogen peroxide to activate the surface of the silicon-based substance, which is conducive to the combination of the silicon-based substance and the organic compound by covalent bonds;

[0120] The organic compound and the mixed intermediate are mixed and ultrasonically treated for 1.0 h to 1.5 h to obtain a silicon-containing material.

[0121] Optionally, based on the total mass of the mixed intermediate, the ratio of the mass content of aqueous ammonia, the mass content of hydrogen peroxide and the mass content of the silicon-based substance is 100:100:(1 to 2).

[0122] In some implementations, step S500 may include:

[0123] The nitrogen-containing material and the silicon-containing material were ultrasonically mixed for 2 to 3 hours, filtered using a polytetrafluoroethylene aluminum membrane and rinsed with deionized water for 3 to 5 times until the pH of the filtrate was 8±0.5, and finally dried in a drying oven at -50°C for 12 hours to obtain a silicon-carbon composite material.

[0124] In the above embodiments, ultrasonic mixing can be used to improve the degree of uniform mixing.

[0125] Negative electrode

[0126] In the third aspect, the present application further provides a negative electrode plate, the negative electrode plate comprising a negative electrode current collector and a negative electrode film layer disposed on at least one side of the negative electrode current collector, the negative electrode film layer comprising a negative electrode active material, the negative electrode active material may comprise the silicon-carbon composite material of any embodiment of the first aspect of the present application, or the silicon-carbon composite material prepared by the method of any embodiment of the second aspect of the present application. The embodiments of the present application are conducive to improving the cycle life and reliability of the battery cell by adding the silicon-carbon composite material to the negative electrode film layer.

[0127] In some embodiments, based on the total mass of the negative electrode film layer, the mass content of the silicon-carbon composite material of the embodiment of the present application is 60% to 100%. Specifically, its mass content can be 60%, 62%, 65%, 68%, 70%, 72%, 75%, 78%, 80%, 82%, 85%, 88%, 90%, 92%, 95%, 98%, 100% or a range consisting of any two of the above values. When the mass content of the silicon-carbon composite material is 100%, it means that the negative electrode film layer is entirely composed of silicon-carbon composite materials. Since the silicon-carbon composite material has a cross-linked structure, it has a certain flexibility, which improves the toughness of the negative electrode film layer and can improve the brittleness and strength of the negative electrode sheet. When the negative electrode sheet is folded in half several times and rolled to crease for brittleness testing, it is found that the crease of the negative electrode sheet is not transparent and does not fall off after the negative electrode sheet is folded in half, and the brittleness of the negative electrode sheet is significantly improved, and the bonding force between the negative electrode film layer and the negative electrode collector is strong.

[0128] In some embodiments, the negative electrode sheet is rolled under a force of 10 tons (10T), and its elongation is 1.5% to 2.5%, optionally 1.8% to 2.5%, and the negative electrode sheet is not broken. The arrangement of the silicon-carbon composite material significantly improves the flexibility of the negative electrode sheet. In particular, when the silicon-carbon composite material has a cross-linked structure, its elongation can be further improved.

[0129] Exemplarily, the elongation of the negative electrode sheet may be 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5% or a range consisting of any two of the above values.

[0130] In the embodiment of the present application, the elongation rate of the negative electrode plate refers to the percentage of the ratio of the length deformation of the negative electrode plate under the action of force to the original length.

[0131] In some embodiments, the negative electrode film layer may further include a negative electrode active material for a battery cell known in the art. As an example, the negative electrode active material may include but is not limited to at least one of natural graphite, artificial graphite, soft carbon, hard carbon, a second silicon-based material, a tin-based material, and lithium titanate. The second silicon-based material may include at least one of elemental silicon, silicon oxide, a silicon-carbon composite, a silicon-nitrogen composite, and a silicon alloy material. The tin-based material may include at least one of elemental tin, tin oxide, and a tin alloy material.

[0132] In some embodiments, the negative electrode film layer may not include a negative electrode binder. Since the silicon-carbon composite material has a cross-linked structure, it has certain flexibility and adsorption capacity, and can be combined with the negative electrode current collector by itself. The bonding force of the negative electrode plate is tested to be 15N / m to 20N / m; it can be optionally 17N / m to 20N / m. The negative electrode film layer has strong bonding properties, and its bonding ability with the negative electrode current collector is strong. The two are not easy to separate, so that the overall structural stability of the negative electrode plate is better.

[0133] Exemplarily, the bonding force of the negative electrode sheet can be 15 N / m, 18 N / m, 20 N / m, 22 N / m, 25 N / m, 26 N / m, 28 N / m, 30 N / m, 32 N / m, 35 N / m, 38 N / m, 40 N / m, 42 N / m, 45 N / m, 48 N / m, 50 N / m, 52 N / m, 55 N / m, 58 N / m, 60 N / m, 62 N / m, 65 N / m, 70 N / m, 75 N / m, 80 N / m, 85 N / m, 90 N / m, or a range consisting of any two of the above values.

[0134] In the embodiments of the present application, the bonding strength of the negative electrode sheet is a well-known meaning in the art, and can be tested using well-known equipment and methods in the art, such as a high-speed rail tensile testing machine. 2 The test specimens of the same size are kept aside for later use; the specimens are bonded to the negative electrode film layer with double-sided tape and compacted with a roller to make the double-sided tape fit the specimen completely; the other side of the double-sided tape of the specimen is pasted to the stainless steel surface, and one end of the specimen is bent in the opposite direction with a bending angle of 180°; the high-speed rail tensile machine is used for testing, one end of the stainless steel is fixed to the clamp below the tensile machine, and the bent end of the specimen is fixed to the clamp above, the angle of the specimen is adjusted to ensure that the upper and lower ends are in a vertical position, and then the specimen is stretched at a speed of 50 mm / min until the specimen is completely peeled off from the stainless steel, and the displacement and force during the process are recorded. It is generally believed that the force when the force is balanced is the bonding force of the negative electrode film layer. The bonding force mainly refers to the bonding force on the side where the negative electrode film layer is set.

[0135] In some embodiments, the compaction density of the negative electrode film layer is 1.8 g×cc -1 To 2.1 g × cc-1 When the compaction density of the negative electrode film layer is within the above range, the coating weight of the negative electrode film layer is relatively high, which is beneficial to improving the energy density of the battery cell.

[0136] For example, the compaction density of the negative electrode film layer may be 1.8 g×cc -1 , 1.9g×cc -1 , 2.0g×cc -1 , 2.1g×cc -1 Or a range consisting of any two of the above values.

[0137] In the embodiments of the present application, the compaction density of the negative electrode film layer is a well-known meaning in the art and can be tested by methods known in the art. For example, a double-roller vertical cold press. Take a single-sided coated and cold-pressed negative electrode pole piece (if it is a double-sided coated pole piece, the negative electrode film layer on one side can be wiped off first), test the thickness of the negative electrode film layer, and then test the surface density of the negative electrode film layer according to the following method: the compaction density of the negative electrode film layer = the surface density of the negative electrode film layer / the thickness of the negative electrode film layer.

[0138] The surface density of the negative electrode film layer is well known in the art and can be tested by methods known in the art. For example, take a negative electrode sheet that has been coated on one side and cold pressed (if it is a negative electrode sheet coated on both sides, the negative electrode film layer on one side can be wiped off first), punch it into small discs with an area of ​​S1, weigh it, and record it as M1. Then wipe off the negative electrode film of the weighed negative electrode sheet, weigh the weight of the negative electrode collector, and record it as M0. The surface density of the negative electrode film layer = (weight of the negative electrode sheet M1-weight of the negative electrode collector M0) / S1.

[0139] In some embodiments, the negative electrode film layer may also optionally include a negative electrode binder. The embodiment of the present application has no particular restrictions on the type of the negative electrode binder. As an example, the negative electrode binder may include at least one of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA) and carboxymethyl chitosan (CMCS). In some embodiments, based on the total mass of the negative electrode film layer, the mass percentage of the negative electrode binder is ≤5%.

[0140] In some embodiments, the negative electrode film layer may further include a negative electrode conductive agent. The embodiment of the present application has no particular restrictions on the type of the negative electrode conductive agent. As an example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. In some embodiments, based on the total mass of the negative electrode film layer, the mass percentage of the negative electrode conductive agent is ≤5%.

[0141] In some embodiments, the negative electrode film layer may further include other additives. As an example, other additives may include thickeners, such as sodium carboxymethyl cellulose (CMC-Na), PTC thermistor materials, etc. In some embodiments, based on the total mass of the negative electrode film layer, the mass percentage of the other additives is ≤2%.

[0142] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0143] The negative electrode current collector has two surfaces opposite to each other in the thickness direction thereof, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector. The relevant parameters mentioned in the embodiments of the present application, such as the mass content of the metal salt in the negative electrode film layer, refer to the mass content of the metal salt in the negative electrode film layer on one side of the negative electrode current collector.

[0144] The negative electrode film layer is usually formed by coating the negative electrode slurry on the negative electrode current collector, drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode film layer, metal salt, optional conductive agent, optional binder, and other optional auxiliary agents in a negative electrode solvent and stirring them evenly. The negative electrode solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto.

[0145] The negative electrode plate does not exclude other additional functional layers in addition to the negative electrode film layer. For example, in some embodiments, the negative electrode plate described in the present application also includes a conductive primer layer (for example, composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector. In some other embodiments, the negative electrode plate described in the present application also includes a protective layer covering the surface of the negative electrode film layer.

[0146] Battery Cell

[0147] In a fourth aspect, the present application provides a battery cell, the battery cell comprising a negative electrode plate. The negative electrode plate can be the negative electrode plate of any embodiment of the third aspect of the present application, and the negative electrode plate can extend the cycle life of the battery cell and improve the reliability of use.

[0148] [Positive electrode]

[0149] In some embodiments, the battery cell further includes a positive electrode tab.

[0150] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material.

[0151] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is disposed on any one or both of the two facing surfaces of the positive electrode current collector.

[0152] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0153] In some embodiments, the positive electrode active material may be a positive electrode active material for a battery cell known in the art. As an example, the positive electrode active material may include at least one of the following materials, a layered positive electrode active material (e.g., ternary, lithium nickelate / sodium, lithium cobaltate / sodium, lithium manganate / sodium, lithium-rich / sodium layered and rock salt phase layered materials), an olivine-type phosphate active material, a spinel structured positive electrode active material (e.g., spinel lithium manganate, spinel nickel lithium manganate, lithium-rich spinel lithium manganate, and lithium nickel lithium manganate, etc.).

[0154] For example, the general formula of the layered positive electrode active material is Li x A y Ni a Co b Mn c M (1-a-b-c) Y z, wherein 0≤x≤2.1, 0≤y≤2.1, and 0.9≤x+y≤2.1; 0≤a≤1, 0≤b≤1, 0≤c≤1, and 0.1≤a+b+c≤1; 1.8≤z≤3.5; A includes one or more of Na, K, and Mg; M includes one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; and Y includes one or more of O and F. Specifically, the layered positive electrode active material may include lithium cobalt oxide LCO, lithium nickel oxide LNO, lithium manganese oxide LMO, and the like.

[0155] Optionally, the layered positive electrode active material is a ternary material, for example, 0<a≤1, 0<b≤1, 0<c≤1, illustratively, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811) and LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523) or more.

[0156] For example, the general formula of the olivine phosphate active material is Li x A y Me a M b P 1-c X c Y z , wherein 0≤x≤1.3, 0≤y≤1.3, and 0.9≤x+y≤1.3; 0.9≤a≤1.5, 0≤b≤0.5, and 0.9≤a+b≤1.5; 0≤c≤0.5; 3≤z≤5; A includes one or more of Na, K, and Mg; Me includes one or more of Mn, Fe, Co, and Ni; M includes one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; X includes one or more of S, Si, Cl, B, C, and N; and Y includes one or more of O and F. Specifically, the olivine-type phosphate active material includes one or more of LiFePO4, LiMnPO4, LiNiPO4, and LiCoPO4.

[0157] For example, the general formula of the positive electrode active material of the spinel structure is Li x Ay Mn a M 2-a Y z , wherein 0≤x≤2, 0≤y≤1, and 0.9≤x+y≤2; 0.5≤a≤2; 3≤z≤5; A includes one or more of Na, K, and Mg; M includes one or more of Ni, Co, B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; and Y includes one or more of O and F. Specifically, the positive active materials of the spinel structure include LiMn2O4, LiNi 0.5 Mn 1.5 O4、LiCr 0.3 Mn 1.7 O4、Li 1.1 Al 0.1 Mn 1.9 O4, Li2Mn2O4 and Li 1.5 One or more of Mn2O4.

[0158] The battery cell will be accompanied by the deintercalation and consumption of active ions such as Li during the charge and discharge process, and the molar content of Li in the battery cell is different when it is discharged to different states. In the list of positive electrode active materials in the embodiments of the present application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode active material is used in the battery system, and the molar content of Li may change after charge and discharge cycles.

[0159] In the list of positive electrode active materials in the embodiments of the present application, the molar content of oxygen O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen O to change. In reality, the molar content of oxygen O will fluctuate.

[0160] In some embodiments, the positive electrode active material layer may further include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0161] In some embodiments, the positive electrode active material layer may further include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0162] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0163] [Electrolyte]

[0164] In some embodiments, the battery cell further includes an electrolyte.

[0165] During the charge and discharge process of the battery cell, active ions are embedded and released back and forth between the positive electrode and the negative electrode, and the electrolyte plays a role in conducting active ions between the positive electrode and the negative electrode. The present application has no particular restrictions on the type of electrolyte, which can be selected according to actual needs.

[0166] The electrolyte solution includes an electrolyte salt and a solvent. The types of the electrolyte salt and the solvent are not specifically limited and can be selected according to actual needs.

[0167] As an example, the electrolyte salt may include, but is not limited to, at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0168] As an example, the solvent may include, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).

[0169] In some embodiments, the electrolyte may further include additives. For example, the additives may include film-forming additives such as positive electrode film-forming additives, etc., and may also include additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, additives that improve battery low temperature power performance, etc.

[0170] [Isolation film]

[0171] In some embodiments, the battery cell further includes a separator.

[0172] The present application has no particular limitation on the type of isolation membrane, and any known porous isolation membrane with good chemical stability and mechanical stability can be selected.

[0173] In some embodiments, the material of the isolation membrane may include at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.

[0174] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet may be formed into an electrode assembly by a winding process and / or a lamination process.

[0175] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.

[0176] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).

[0177] The present application has no particular restrictions on the shape of the battery cell, which can be cylindrical, square or any other shape. Figure 1 The battery cell 5 is a square structure as an example.

[0178] In some embodiments, Figure 2As shown, the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can form an electrode assembly 52 through a winding process and / or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be adjusted according to demand.

[0179] The preparation method of the battery cell of the present application is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a battery cell. As an example, the positive electrode sheet, the separator and the negative electrode sheet can be formed into an electrode assembly through a winding process and / or a lamination process, and the electrode assembly is placed in an outer package, and the electrolyte is injected after drying, and the battery cell is obtained through vacuum packaging, standing, forming, shaping and other processes.

[0180] In some embodiments of the present application, the battery cells according to the present application may be assembled into a battery module. The battery module may contain multiple battery cells, and the specific number may be adjusted according to the application and capacity of the battery module.

[0181] Figure 3 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 3 As shown, in the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.

[0182] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.

[0183] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0184] Figure 4 and Figure 5 FIG. 1 is a schematic diagram of a battery pack 1 as an example. Figure 4 and Figure 5 As shown, the battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3, wherein the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.

[0185] The battery according to the embodiment of the present application may include one battery cell or a plurality of battery cells. When the battery includes a plurality of battery cells, the battery may include a battery module or a battery pack.

[0186] Electrical devices

[0187] The fifth aspect of the embodiment of the present application provides an electric device, which includes at least one of the battery cells, battery modules or battery packs of the present application. The battery cells, battery modules or battery packs can be used as the power source of the electric device, and can also be used as the energy storage unit of the electric device. The electric device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.

[0188] The electrical device may select a battery cell, a battery module or a battery pack according to its usage requirements.

[0189] Figure 6 Schematic diagram of an exemplary electric device 6. The electric device 6 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the requirements of the electric device 6 for high power and high energy density, a battery pack or a battery module may be used.

[0190] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a battery cell may be used as a power source.

[0191] Example

[0192] The following embodiments describe the contents disclosed in the present application in more detail, and these embodiments are only used for illustrative explanations, because it is obvious to those skilled in the art that various modifications and changes are made within the scope of the present application disclosure. Unless otherwise stated, all parts, percentages and ratios reported in the following embodiments are based on mass, and all reagents used in the embodiments are commercially available or synthesized according to conventional methods, and can be used directly without further processing, and the instruments used in the embodiments are commercially available.

[0193] Preparation of Silicon Carbon Composite Materials

[0194] Step 1, mixing the carbon-based substance and the mixed acid, ultrasonically treating the mixture for 3 hours, filtering the mixture with a polytetrafluoroethylene filter membrane, and rinsing the mixture with deionized water for 5 times until the pH value of the filtrate is 6±0.5, and drying the mixture in a freeze drying oven at -50°C for 12 hours to obtain a carbon-containing material; wherein the mass content ratio of the carbon-based substance to the mixed acid is (1 to 2):200; the mixed acid includes concentrated sulfuric acid and concentrated nitric acid, and the mass ratio thereof is 1:1;

[0195] Step 2, mixing ammonia water, hydrogen peroxide and silicon-based substance and ultrasonically treating them for 40 minutes for later use; wherein the mass content ratio of ammonia water, hydrogen peroxide and silicon-based substance is 100:100:(1 to 2);

[0196] Step 3, mixing a 20% aqueous solution of an organic compound with the product of step 2, and continuing ultrasonic treatment for 1.5 hours to obtain a silicon-containing material; wherein the mass content ratio of the organic compound to the silicon-based substance is (1 to 5): 1;

[0197] Step 4: Add the product of step 1 to the reactor of step 3, continue ultrasonic mixing for 2.5 hours, filter using a polytetrafluoroethylene aluminum membrane and rinse with deionized water 4 times until the pH of the filtrate is 8±0.5, and finally dry in a drying oven at -50°C for 12 hours to obtain a silicon-carbon composite material.

[0198] Preparation of lithium-ion batteries

[0199] 1. Preparation of positive electrode

[0200] Aluminum foil with a thickness of 12 μm was used as the positive electrode current collector.

[0201] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent conductive carbon black, and binder polyvinylidene fluoride (PVDF) are mixed evenly in a proper amount of solvent N-methylpyrrolidone (NMP) in a mass ratio of 85:10:5 to obtain positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained through processes such as drying, cold pressing, slitting, and cutting.

[0202] 2. Preparation of negative electrode sheet

[0203] A copper foil with a thickness of 8 μm was used as the negative electrode current collector.

[0204] The silicon-carbon composite material as the negative electrode active material, the conductive agent conductive carbon black, polyacrylic acid (PAA) and the binder sodium carboxymethyl cellulose (CMC-Na) were mixed evenly in deionized water at a mass ratio of 92:2:3:3 to prepare a negative electrode slurry. The negative electrode slurry was coated on the current collector copper foil and dried at 85°C and cold pressed to obtain a negative electrode sheet containing a negative electrode film layer.

[0205] 3. Preparation of electrolyte

[0206] In an environment with a water content of less than 10ppm, organic solvents ethylene carbonate EC and diethyl carbonate DEC are mixed in a volume ratio of 3:7 to obtain an electrolyte solvent, and then lithium salt lithium hexafluorophosphate is added to the mixed solvent, stirred evenly, to prepare an electrolyte with a lithium salt concentration of 1 mol / L.

[0207] 4. Preparation of lithium-ion batteries

[0208] The positive electrode sheet, polyethylene PE separator, and negative electrode sheet are stacked and wound in order to obtain an electrode assembly; the electrode assembly is placed in an outer package, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0209] Example 1

[0210] In silicon-carbon composite materials, the carbon-based material is single-walled carbon nanotubes, and the silicon-based material is silicon nanowires.

[0211] The mass content ratio of the carbon-based substance to the mixed acid is 1:200.

[0212] The mass content ratio of ammonia water, hydrogen peroxide and silicon-based substances is 100:100:1.5.

[0213] The mass content ratio of the organic compound PDDA and the silicon-based substance is 2:1.

[0214] The mass content ratio of the carbon-containing material to the silicon-containing material is 5:1.

[0215] Example 2-1 to Example 2-5

[0216] Different from Example 1, in the silicon-carbon composite materials of Examples 2-1 to 2-5, the type of at least one of the carbon-based material and the silicon-based material is adjusted.

[0217] Example 3-1 and Example 3-2

[0218] Different from Example 1, in the silicon-carbon composite materials of Examples 3-1 and 3-2, the types of groups on the surface of the carbon-based substances are adjusted.

[0219] Example 4-1 and Example 4-2

[0220] Different from Example 1, in the silicon-carbon composite materials of Examples 4-1 and 4-2, the substance types of the organic compounds on the surface of the silicon-based material are adjusted.

[0221] Example 5-1 and Example 5-2

[0222] Different from Example 1, in the silicon-carbon composite materials of Example 5-1 and Example 5-2, the mass ratio of the carbon-based substance and the mixed acid was adjusted, thereby adjusting the number of negatively charged groups on the surface of the carbon-based substance.

[0223] In Example 5-1, the mass ratio of the carbon-based substance to the mixed acid is 1:100, and the number of negatively charged groups in Example 5-1 is less than that in Example 1;

[0224] In Example 5-2, the mass ratio of the carbon-based substance to the mixed acid is 1:150. The number of negatively charged groups in Example 5-2 is less than that in Example 1, but more than that in Example 5-1.

[0225] Example 6-1 and Example 6-2

[0226] Different from Example 1, in the silicon-carbon composite materials of Example 6-1 and Example 6-2, the mass ratio of the silicon-based substance and PDDA (or ammonia water, hydrogen peroxide and silicon-based substance) was adjusted, thereby adjusting the number of positively charged groups on the surface of the silicon-based substance.

[0227] Example 6-1

[0228] The mass content ratio of ammonia water, hydrogen peroxide and silicon-based substances is 100:100:1;

[0229] The mass content ratio of the organic compound PDDA and the silicon-based substance is 1:1; the number of positively charged groups in Example 6-1 is less than that in Example 1.

[0230] Example 6-2

[0231] The mass content ratio of ammonia water, hydrogen peroxide and silicon-based substances is 100:100:2.

[0232] The mass content ratio of the organic compound PDDA and the silicon-based substance is 5:1; the number of positively charged groups in Example 6-2 is greater than that in Example 1.

[0233] Example 7-1 to Example 7-3

[0234] Different from Example 1, in the silicon-carbon composite materials of Examples 7-1 to 7-3, the mass content ratio of the carbon-containing material to the silicon-containing material is adjusted.

[0235] Comparative Example 1

[0236] Different from Example 1, the silicon-carbon composite material of Comparative Example 1 is prepared by the following steps:

[0237] The carbon-based material and the carbon-based material were added to NMP in a mass ratio of 5:1 and ultrasonically mixed for 2.5 h. Finally, the mixture was dried in a drying oven at -50°C for 12 h to obtain a silicon-carbon composite material.

[0238] Comparative Example 2

[0239] Different from Example 1, the silicon-carbon composite material of Comparative Example 2 is prepared by the following steps:

[0240] Step 1, mixing the carbon-based substance and the mixed acid, ultrasonically treating the mixture for 3 hours, filtering the mixture with a polytetrafluoroethylene filter membrane, and rinsing the mixture with deionized water for 5 times until the pH value of the filtrate is 6±0.5, and drying the mixture in a freeze drying oven at -50°C for 12 hours to obtain a carbon-containing material; wherein the mass content ratio of the carbon-based substance to the mixed acid is 1:200; and the mixed acid includes concentrated sulfuric acid and concentrated nitric acid, and the mass ratio thereof is 1:1;

[0241] Step 2: Add the silicon-based substance to the product of step 1, continue ultrasonic mixing for 2.5 hours, filter using a polytetrafluoroethylene aluminum membrane and rinse with deionized water 4 times until the pH of the filtrate is 8±0.5, and finally dry in a drying oven at -50°C for 12 hours to obtain a silicon-carbon composite material.

[0242] Comparative Example 3

[0243] Different from Example 1, the silicon-carbon composite material of Comparative Example 3 is prepared by the following steps:

[0244] Step 1, mixing ammonia water, hydrogen peroxide and silicon-based substance, and then ultrasonically treating for 40 minutes for standby use; wherein the mass content ratio of ammonia water, hydrogen peroxide and silicon-based substance is 100:100:1.5;

[0245] Step 2, mixing a 20% PDDA aqueous solution with the product of step 1, and continuing ultrasonic treatment for 1.5 hours to obtain a silicon-containing material; wherein the mass content ratio of PDDA to the silicon-based substance is 2:1;

[0246] Step 3, add the carbon-based material to the reactor of step 3, continue ultrasonic mixing for 2.5 hours, filter using a polytetrafluoroethylene aluminum membrane and rinse with deionized water 4 times until the pH of the filtrate is 8±0.5, and finally dry in a drying oven at -50°C for 12 hours to obtain a silicon-carbon composite material.

[0247] The relevant parameters of the embodiments and comparative examples are shown in Table 1.

[0248] Test Section

[0249] 1. Cycle performance test of lithium-ion batteries

[0250] At 25°C, the lithium ion batteries prepared in the examples and comparative examples were charged to 4.0V at a charge rate of 0.33C, and discharged to 2.0V at a rate of 0.33C. A full charge and discharge cycle test was performed. The capacity of the lithium ion battery decayed to 80% of the initial capacity, and the number of cycles was recorded.

[0251] 2. Dynamic performance test of lithium-ion batteries

[0252] At 25°C, the lithium-ion battery prepared in the embodiment and the comparative example was fully charged at 2C and fully discharged at 1C for 5 times, and then the lithium-ion battery was fully charged at 2C, and then the negative electrode plate was disassembled and the lithium deposition on the surface of the negative electrode plate was observed. Among them, the area of ​​lithium deposition on the negative electrode surface is less than 5%, which is considered to be slight lithium deposition (it can be considered that no lithium deposition occurs during fast charging), the area of ​​lithium deposition on the negative electrode surface is 5% to 40%, which is considered to be moderate lithium deposition (it can be considered that lithium deposition occurs during fast charging), and the area of ​​lithium deposition on the negative electrode surface is greater than 40%, which is considered to be severe lithium deposition (it can be considered that lithium deposition occurs during fast charging).

[0253] Test Results

[0254] The test results are shown in Table 1

[0255] Table 1

[0256]

[0257] As shown in Table 1, in Comparative Example 1, by physically mixing single-walled carbon nanotubes and silicon nanowires, the binding effect of single-walled carbon nanotubes on silicon nanowires is weak, and the volume expansion effect of silicon nanowires cannot be well alleviated, which may lead to deterioration of the performance of lithium-ion batteries.

[0258] Compared with Comparative Example 1, Comparative Example 2 modifies the surface of the single-walled carbon nanotube with negatively charged groups. Since the interaction between the negatively charged groups and the silicon nanowires is weak, the binding effect of the single-walled carbon nanotubes on the silicon nanowires is still weak, and the volume expansion effect of the silicon nanowires cannot be well alleviated. Compared with Comparative Example 1, Comparative Example 3 modifies the surface of the silicon nanowire with positively charged groups. Since the interaction between the single-walled carbon nanotubes and the positively charged groups of the silicon nanowires is weak, the binding effect of the single-walled carbon nanotubes on the silicon nanowires is still weak, and the volume expansion effect of the silicon nanowires cannot be well alleviated.

[0259] The embodiments of the present application modify the surface of single-walled carbon nanotubes with negatively charged groups and the surface of silicon nanowires with positively charged groups, and composite the carbon-containing material and the silicon-containing material through electrostatic action. The silicon-containing material is surrounded by the carbon-containing material. The carbon-containing material acts as a buffer layer for silicon expansion, which can reduce the risk of silicon expansion, thereby reducing the risk of silicon-containing material being pulverized, and improving the overall structural stability of the silicon-carbon composite material. The organic compound on the surface of the silicon-containing material can enhance the physical crosslinking with the carbon-containing material, and the structural strength of the silicon-carbon composite material formed by the composite of the two is further improved, thereby taking into account the improvement of the cycle life of the battery cell. It can be seen from Examples 5-1 and 5-2, and Examples 6-1 and 6-2 that as the number of charged groups on the surface of the carbon-containing material and / or the silicon-containing material increases within a certain range, the binding force between the two can be improved, thereby improving the cycle performance of the battery cell.

[0260] Figure 7 The preparation process of the silicon-carbon composite material of Example 1 is described. Figure 8 This is the infrared spectrum of the single-walled carbon nanotubes MWCTN after acid treatment in Example 1. -1 A strong -OH stretching vibration peak of phenols was found near 1100 cm -1 The stretching vibration peak of the hydroxyl carbon oxygen (CO) of the nearby alcohol. The infrared results show that a large number of hydroxyl groups appear on the surface of MWCTN after acid treatment. Fig. 9 These are the zeta potential test results of MWCNT after acid treatment and silicon nanowire PDDA-Si treated with PDDA. The results show that MWCNT has a negative charge after acid treatment, and the surface of PDDA-Si has a positive charge.

[0261] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present application, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present application.

Claims

1. A silicon-carbon composite material, comprising: A carbon-containing material, comprising a carbon-based substance and a first group disposed on the surface of the carbon-based substance; as well as The silicon-containing material comprises a silicon-based substance and an organic compound coated on at least a part of the surface of the silicon-based substance, wherein the organic compound and the first group have opposite electrical properties and are combined with the first group through electrostatic interaction.

2. The silicon-carbon composite material according to claim 1, wherein: The first group is an electronegative group; Optionally, the first group includes at least one of a hydroxyl group, an amino group, an alkyl group, an acyloxy group and an alkoxy group.

3. The silicon-carbon composite material according to claim 1 or 2, wherein: The organic compound includes at least one of polydiallyldimethylammonium chloride, polyacrylamide and polydimethyldiallylammonium chloride.

4. The silicon-carbon composite material according to any one of claims 1 to 3, wherein The carbon-based material includes at least one of natural graphite, artificial graphite, graphene, carbon nanotubes and carbon fibers; and / or The silicon-based material includes at least one of silicon and silicon oxide; Optionally, the silicon element includes at least one of silicon nano-element and silicon micro-element; Further optionally, the silicon nano-element includes at least one of silicon nanoparticles, silicon nanowires and silicon nanosheets.

5. The silicon-carbon composite material according to claim 4, wherein: The carbon-based substance includes at least one of carbon nanotubes and carbon fibers; optionally, the carbon nanotubes include at least one of single-walled carbon nanotubes and multi-walled nanotubes; The silicon-based substance includes silicon nanoparticles; optionally, the silicon-based substance includes silicon nanowires.

6. The silicon-carbon composite material according to any one of claims 1 to 5, wherein: Based on the total mass of the silicon-carbon composite material, the ratio of the mass content of the carbon-containing material to the mass content of the silicon-containing material is (3 to 5): 1; Optionally, The mass content of the carbonaceous material is 75% to 85%; and / or The mass content of the silicon-containing material is 15% to 25%.

7. The silicon-carbon composite material according to any one of claims 1 to 6, wherein: Based on the total mass of the silicon-carbon composite material, the ratio of the mass content of the organic compound to the mass content of the silicon-based substance is (1 to 5): 20; Optionally, The mass content of the organic compound is 1% to 5%; and / or The mass content of the silicon-based substance is 15% to 20%.

8. The silicon-carbon composite material according to any one of claims 1 to 7, wherein: The silicon-carbon composite material satisfies at least one of conditions (1) to (3): (1) The volume average particle size Dv50 of the silicon-carbon composite material is 1 μm to 5 μm; (2) The BET specific surface area of ​​the silicon-carbon composite material is 200 m 2 / g to 400m 2 / g; (3) The electrical conductivity of the silicon-carbon composite material is 120 S / cm to 3000 S / cm; optionally, 300 S / cm to 3000 S / cm.

9. A method for preparing a silicon-carbon composite material, comprising: Provide carbon-based substances; The carbon-based substance is subjected to a grouping treatment so that the surface of the carbon-based substance has a first group and forms a carbon-containing material; Providing silicon-based substances; Providing an organic compound to the silicon-based material for grouping treatment, so that at least a portion of the surface of the silicon-based material is coated with the organic compound to form a silicon-containing material, wherein the electrical properties of the organic compound and the first group are opposite; The carbon-containing material and the silicon-containing material are mixed to obtain a silicon-carbon composite material, wherein the first group and the organic compound are combined by electrostatic interaction.

10. A negative electrode plate, comprising a negative electrode current collector and a negative electrode film layer arranged on at least one side of the negative electrode current collector, wherein the negative electrode film layer comprises the silicon-carbon composite material as described in any one of claims 1 to 8, or the silicon-carbon composite material prepared by the method as described in claim 9.

11. The negative electrode sheet according to claim 10, wherein: The bonding force of the negative electrode plate is 15 N / m to 20 N / m; optionally 17 N / m to 20 N / m; and / or The negative electrode plate is 1×10 4 Under a force of Kg (10T), the elongation is 1.5% to 2.5%; optionally, 1.8% to 2.5%. 12 . A battery cell comprising the negative electrode sheet according to claim 10 or 11 .

13. An electrical device comprising the battery cell according to claim 12.

Citation Information

Patent Citations

  • Silicon-carbon composite material, preparation method thereof and lithium ion battery

    CN112002885A

  • Silicon-carbon composite material, preparation method thereof and lithium ion battery

    CN113193185A

  • Negative electrode material, negative electrode sheet, electrochemical device, and electronic device

    CN113728471A